A High-Resolution Physical and Transcript Map of the Cri du Chat Region of Human Chromosome 5p - Church, Deanna M.; Yang, Julie; Bocian, Maureen; Shiang, Rita; Wasmuth, John J.

(untitled) (Genome Research, 1997)
A high-resolution physical and transcription map has been generated of a 3.5-Mb region of 5p15.2 that is associated with the Cri du chat (CDC) syndrome. Utilizing a variety of resources including a natural deletion panel, a chromosome specific radiation hybrid panel, and YAC, PAC, and BAC genomic clones we have ordered >60 STSs within this region. Approximately 45% of these STSs were obtained from publicly available whole genome maps, thus allowing for integration of this map with currently available resources. Thirteen of these markers were ESTs. In addition, >70 exon trapped products have been mapped on the natural deletion panel and bacterial clone resource. The combination of these resources has allowed for the identification of 17 transcripts within this region, all of which represent candidate genes for CDC. Further characterization of the genomic contig also revealed that this region of 5p15 contains a large number of repetitive elements.[The sequence data described in this paper have been submitted to GenBank under accession nos. G31374–G31412,B07604–B07657. On-line supplementary material concerning markers used, primers, PCR product sizes, and annealing conditions is available athttp://www.cshl.org/gr.]